ASSESSMENT OF THE EFFECTS OF CLIMATE CHANGE ON THE LIVELIHOODS AND ADAPTATION STRATEGIES OF RURAL WOMEN IN KWARA STATE, NIGERIA - O. J. Yusuf; L. K. Olatinwo; O. E. Aiyedun (مجلة الأنبار للعلوم الزراعية)
This study investigated the effects of climate change on the livelihoods and adaptation strategies of rural women in Kwara State, Nigeria, analyzing data from 124 women farmers through a structured questionnaire and employing descriptive statistics and regression analysis. The findings highlighted significant impacts of climate change, including reduced crop yields (mean score = 4.39), decreased quantity and quality of grass and forage (mean score = 4.77), limited water supply for livestock and human use (mean score =4.65), and diminished social status due to restricted access to land and water resources (mean score =4.44). Notably, the positive relationship between adaptation strategies (β = 0.454, p <0.01) and perceived effects of climate change indicates that as women adopt more effective adaptation measures, their awareness of climate change impacts increases, suggesting that these strategies not only help mitigate adverse effects but also enhance their understanding of climate-related challenges. Conversely, the small coefficient for age (β = -0.007) implies that while older age is associated with a slight decrease in perceived climate change effects, this relationship is practically insignificant. This suggests that age alone does not play a substantial role in shaping perceptions, highlighting the need for more impactful factors, such as experience and access to resources, to be considered in addressing the challenges posed by climate change. The study concludes that climate change has severely affected the livelihoods of rural women, emphasizing the need for targeted interventions. To enhance resilience, agricultural extension services, and women's empowerment programs are recommended to prioritize initiatives promoting climate-resilient crop production practices